The Experimental and Theoretical Study in Performance of Chilled Ceiling - Ali AbdulGhafor, Israa; S. Mehdi, Qasim; A. Abdulrasool, Adnan. (International Journal of Engineering and Technology, 2018)
The present study represents the experimental study for the performance of the chilled ceiling and it ability to achieve thermal condition in occupied zone. The experimental study included the effect of different internal load of (1600, 1300and 1000) W and different supplied chilled water temperatures of (13.3, 14.2, 16.8 and 18)Â°C on the performance of chilled ceiling. The experimental results show that the cooling capacity of chilled ceiling increases as temperature of supplied water decreases. For decreases in Â temperature ofÂ supplied chilled water by 33.5%,the cooling capacity of chilled ceiling Â is increasedÂ by 18.73%.This study presented theoretical study of velocity and temperature distributionÂ Â in occupied zone when using chilled ceiling.Â